2023
DOI: 10.1101/2023.03.07.531490
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel axonemal protein ZMYND12 interacts with TTC29 and DNAH1, and is required for male fertility and flagellum function

Abstract: Male infertility is common and complex, presenting a wide range of heterogeneous phenotypes. Although about 50% of cases are estimated to have a genetic component, the underlying cause often remains undetermined. Here, from whole-exome sequencing on samples from 168 infertile men with severe sperm flagellum defects, we identified homozygous ZMYND12 variants in four unrelated patients. In sperm cells from these individuals, immunofluorescence revealed altered localization of DNAH1, DNALI1, WDR66 and TTC29. Axon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 72 publications
3
6
0
Order By: Relevance
“…Coutton et al recently found that 3 of 167 patients with MMAF harbored variants in the ZMYND12 gene [21]. In line with its possible functional role in this context, knockdown of the ZMYND12 ortholog TbTAX-1 in Trypanosoma brucei had a pronounced effect on sperm motility [21,22]. These results suggest a potential role for ZMYND12 de ciency in human AZS.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Coutton et al recently found that 3 of 167 patients with MMAF harbored variants in the ZMYND12 gene [21]. In line with its possible functional role in this context, knockdown of the ZMYND12 ortholog TbTAX-1 in Trypanosoma brucei had a pronounced effect on sperm motility [21,22]. These results suggest a potential role for ZMYND12 de ciency in human AZS.…”
Section: Introductionmentioning
confidence: 83%
“…Prior studies identi ed p38 in Chlamydomonas as an IDAdspeci c accessory subunit [20]. Coutton et al recently found that 3 of 167 patients with MMAF harbored variants in the ZMYND12 gene [21]. In line with its possible functional role in this context, knockdown of the ZMYND12 ortholog TbTAX-1 in Trypanosoma brucei had a pronounced effect on sperm motility [21,22].…”
Section: Introductionmentioning
confidence: 98%
“…Of note, many genetic changes identified in this study have been closely associated with sperm formation. For example, Zmynd12 (29), Bbs7 (30), and Ube2j2 (18) were required for flagellum function and male fertility. Map7d1 facilitates microtubule stabilization (31) and Mfn1 deficiency leads to defects in mitochondrial activity and male infertility (32).…”
Section: Discussionmentioning
confidence: 99%
“…Many proteins with unknown roles and locations are also depleted or reduced (Figure 2C). Inspection of single particle cryo-EM reconstructions shows that at least 13 of the missing proteins are in direct contact with the CCDC39/40 heterodimer (Figure 2C) [7][8][9][10][11][12]14,[45][46][47][48][49][50][51][52][53][54][55] . Each of these 13 missing proteins, plus MORN3, which is not present in our proteomics, is linked to a major cilia complex (Figure 2D).…”
Section: B)mentioning
confidence: 99%
“…Notably, 14 of the missing proteins directly contact CCD39/40 and are likely to be the ciliary address recognition proteins (CARPs) for IDA, the N-DRC, and the RSs. CARPs attach to specific amino acid sequences of CCDC39/40 (the addresses) (Figure 2D, 2E) [7][8][9][10][11][12]14,[45][46][47][48][49][50][51][52][53][54][55] . During assembly, CARPs enter cilia coincident with CCDC39/40.…”
Section: Ciliary Address Recognition Proteins (Carp) Identify Address...mentioning
confidence: 99%